Distribution of Genus Cookeina and Ethnomycology in Indonesia - Putra, Ivan Permana; Murung, Hari Gloria Riwut Teka (RUMPHIUS, 2025)
Wild edible mushrooms are germplasm which widely consumed by various local communities around the world. One of the wild mushroom genera that grows wild and used as food is Cookeina. This mushroom has the shape of bowl, glass, or cup which grows saprophyticly on the stems or seeds of forestry plants. However, the information of Cookeina potency as an alternative food is scarce in Indonesia. This is due to the lack of reports on the use of this macrofungi for consumption in Indonesia. In addition, most of the reports are not provided with the descriptions of the mushrooms. As the result, it as a serious constrain to non mycologyst person or mushroom hobyyist to study Cookeina. This manuscript aimed to provide the information on the distribution of this mushroom in Indonesia, the description of the morphological characters, and examples of the use of Cookeina as food by local communities (ethnomicology). This macrofungi have been reported 16 times in Indonesia, spread over 10 different provinces. The species which have been reported are C. colensoi, C. speciosa, C. sulcipes, and C. tricholoma in Indonesia. However, only C. speciosa, C. sulcipes, and C. tricholoma which used ad food and medicine by indigenous peoples in Indonesia. Several studies in various countries have proven that Cookeina contains bioactive ingredients in the form of β-glucan which are good for health. It is hoped that the level of awareness of the Indonesian people will increase regarding the potential use of edible wild mushrooms in order to achieve the food sovereignty.